2011
DOI: 10.1002/rnc.1713
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of switching networks of multi‐agent systems

Abstract: SUMMARY This paper addresses the controllability of a switching network of multi‐agent systems with a leader obeying nearest‐neighbor communication rules. The leader is a particular agent acting as an external input to control other member agents. Some computationally efficient sufficient conditions for such multi‐agent systems to be controllable are derived. The results show that a multi‐agent system can be controllable even if each of its subsystem is not controllable, by appropriately selecting one of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 30 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…For example, we develop the flag union graph and the flag distance in the proof of Theorem 2. Compared with the existing literature,() it is shown that our results are applicable to systems with arbitrary switching directed topology rather than directed fixed topology. Specifically, we show that our results are valid for arbitrary coupling weights.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…For example, we develop the flag union graph and the flag distance in the proof of Theorem 2. Compared with the existing literature,() it is shown that our results are applicable to systems with arbitrary switching directed topology rather than directed fixed topology. Specifically, we show that our results are valid for arbitrary coupling weights.…”
Section: Introductionmentioning
confidence: 81%
“…A natural framework to study the time variance of communication topology is through switched systems. In other works,() some algebraic conditions were proposed for the controllability of multiagent systems with switching topology. In the works of Liu et al,() the authors proved that the controllability of the overall system does not depend on that of each subsystem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, tree graph was studied in , and necessary and sufficient conditions were proposed in terms of downer branch and subgraphs to characterize controllability. In addition, there are some other relevant results, for example, results on controllability were derived with respect to protocols design , heterogeneous dynamics , identification of topology structures , switching topology , time‐delay and structural controllability , and so on.…”
Section: Introductionmentioning
confidence: 99%